Performance of Prostate Imaging Reporting and Data System Version 2.1 for Diagnosis of Prostate Cancer: A Systematic Review and Meta‐Analysis. Issue 1 (11th February 2021) - Park, Kye Jin; Choi, Sang Hyun; Kim, Mi‐hyun; Kim, Jeong Kon; Jeong, In Gab
Abstract : Background: The Prostate Imaging Reporting and Data System (PI‐RADS) was introduced in 2012 and updated to version 2.1 (v2.1) in early 2019 to improve diagnostic performance and interreader reliability. Purpose: To evaluate the diagnostic performance of PI‐RADS v2.1 in comparison with v2. Methods: A systematic review and meta‐analysis of the literature was performed using MEDLINE, EMBASE, and Cochrane databases to identify studies evaluating the diagnostic performance of PI‐RADS v2.1 for diagnosing clinically significant prostate cancer (csPCa). Study Type: Systematic review and meta‐analysis. Subject: One thousand two hundred forty‐eight patients with 1406 lesions from 10 eligible articles. Field Strength/sequence: Conventional MR sequences at 1.5 T and 3 T. Assessment: Two reviewers independently identified and reviewed the original articles reporting diagnostic performance of PI‐RADS v2.1. Statistical Tests: Meta‐analytic summary sensitivity and specificity were calculated using a bivariate random effects model. Meta‐analytic sensitivity and specificity between PI‐RADS v2 and v2.1 were compared. Results: The pooled sensitivity and specificity of PI‐RADS v2.1 were 87% (95% confidence intervals, 82–91%) and 74% (63–82%), respectively. In five studies available for a head‐to‐head comparison between PI‐RADS v2.1 and v2, there were no significant differences in either sensitivity (90% [86–94%] vs. 88% [83–93%], respectively) or specificity (76% [59–93%] vs. 61% [39–83%], respectively; P = 0.37). The sensitivity and specificity were 81% (73–87%) and 82% (68–91%), respectively, for a PI‐RADS score cutoff of ≥4, and 94% (88–97%) and 56% (35–97%) for ≥3. Regarding the zonal location, the sensitivity and specificity for the transitional zone only were 90% (84–96%) and 76% (62–90%) respectively, whereas for the whole gland they were 85% (79–91%) and 71% (57–85%). Data Conclusion: PI‐RADS v2.1 demonstrated good overall performance for the diagnosis of csPCa. PI‐RADS v2.1 tended to show higher specificity than v2, but the difference lacked statistical significance. Level of Evidence: 3 Technical Efficacy Stage: 3